Pembelajaran Tematik Terpadu dengan Menggunakan Model Quantum Teaching - Nadya Yolanda; Reinita Reinita (Journal of Elementary School (JOES), 2019)
This study aims to describe the improvement of integrated thematic learning processes using the Quantum Teaching model in class V SD N 16 Koto Baru Solok. This type of research is Classroom Action Research (CAR). Subjects in the study were 22 teachers and students. Research site at SD N 16 Koto Baru Solok. The results showed an increase in: a) RPP cycle I with an average of 80.05% and cycle II 97.22%, b) Implementation of the aspects of the teacher Idengan cycle on average was 77.77% and cycle II 94, 44%, while the implementation of aspects of the first cycle students with an average of 79.1% and the second cycle 94.44% (very good), d) Assessment of student learning outcomes in the first cycle with an average of 72.9 and the cycle II 94. Conclusion, that the application of the Quantum Teaching model shows an increase in student learning outcomes and processes in integrated thematic learning. Keyword : Quantum Teaching; integrated thematic